UNLOCKING LEARNING OPPORTUNITIES WITH INTERACTIVE GAMES - Bektosh Norbo’tayevich Tursunboev (Western European Studies, 2024)
Addressing the challenge of maintaining creativity in teaching and overcoming student boredom, this study explores the use of interactive games to enhance the learning environment. Factors such as class size, learning schedules, and intellectual diversity are examined, with a focus on how games can serve as effective teaching strategies. Interactive games, including traditional board games and digital simulations, are shown to engage students, foster collaboration, and provide personalized learning experiences. The research specifically investigates the impact of the "Find Someone Who..." game on 15 students at the Wonders Language Center, assessing its effects on motivation and linguistic complexity in learning English as a Foreign Language (EFL). Using observation, interviews, and questionnaires, the study finds that the game promotes active participation, reduces anxiety, and increases motivation among students. These results highlight the broader benefits of interactive games, including the development of essential life skills and the creation of dynamic, effective, and contextually rich learning environments. The study concludes that interactive games are a powerful pedagogical tool for EFL teaching, offering a holistic and enjoyable approach to language acquisition.
Keywords: Engagement; collaboration; creativity; problem-solving